2008
DOI: 10.1111/j.1365-2621.2006.01386.x
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of chemical preservatives with ethanol on the microbial shelf life of bread by factorial design

Abstract: The shelf life, particularly the mould-free shelf life (MFSL) of bread, was evaluated either by adding a conventional chemical preservative or by spraying the surface of bread, in which a chemical preservative was added. As bread making is a complex process and bread is a multicomponent system, the investigation was based on statistical design experiments. Using first-order factorial designs, reliable models were constructed, revealing the effects of some common ingredients of bread (such as salt, sugar, glyce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 14 publications
2
11
0
Order By: Relevance
“…From the results, it can be seen that the TPC exceeded the value of 6 log cfu/g on day 2 for air‐packaged samples, day 7 for samples containing OA, day 12 for samples containing OA + EE (1%) and day 19 for samples containing OA + EE (3%). The samples having active packaging had a higher microbiological inhibition compared to the control, which could be attributed to the protective effect of OA against strictly aerobic organisms and the antimicrobial activity of ethanol . With respect to the use of OA, the present results concur with those of Mexis et al .…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…From the results, it can be seen that the TPC exceeded the value of 6 log cfu/g on day 2 for air‐packaged samples, day 7 for samples containing OA, day 12 for samples containing OA + EE (1%) and day 19 for samples containing OA + EE (3%). The samples having active packaging had a higher microbiological inhibition compared to the control, which could be attributed to the protective effect of OA against strictly aerobic organisms and the antimicrobial activity of ethanol . With respect to the use of OA, the present results concur with those of Mexis et al .…”
Section: Resultssupporting
confidence: 89%
“…The samples having active packaging had a higher microbiological inhibition compared to the control, which could be attributed to the protective effect of OA against strictly aerobic organisms 17 and the antimicrobial activity of ethanol. 30 With respect to the use of OA, the present results concur with those of Mexis et al 9 who reported that air-packaged ground chicken had a shelf-life of 3-4 days while samples containing OA had an extended shelf-life of 6-7 days. They are also in agreement with those of Gonçalves et al 31 who reported that a reduction of 2 log cfu/g of TPC in gilthead seabream containing OA was observed, as compared to control samples.…”
Section: Microbiological Changessupporting
confidence: 91%
“…Ethanol concentrations ranging between 0.2% and 12% are reported to increase bread shelf-life [30]. Moreover, its addition on bread surface (0.5% w/w) contributes to improving sorbate and propionate effect [31]. Berni and Scaramuzza (2013) [32] have recently observed ethanol potential to inhibit Crysonilia sitophila, more commonly known as "the red bread mould", and H. burtoni, also known as "the chalky mould", on packed and sliced bread at very low (0.8%) and medium (2.0%) ethanol concentrations, respectively.…”
Section: Chemical Treatmentsmentioning
confidence: 99%
“…; Katsinis et al . ; Latou et al . ), and studies concerning the effect of ethanol on bakery‐associated moulds have not been carried out so far.…”
Section: Resultsmentioning
confidence: 99%
“…; Katsinis et al . ). For this reason, it is frequently added as a preservative by bakery industries in foods where reduction in fungal contamination or inhibition of fungal growth is needed (Daifas et al .…”
Section: Introductionmentioning
confidence: 97%